Adversity Quotient and Metacognion as Related to Mathematics Performance - Judy D. Jemina; June Rey S. Sulatra (Researchparks Publishing, 2022)
This descriptive ascertained the relationship of adversity quotient and metacognition to mathematics performance students. There were three hundred (300) respondents who were randomly selected from two high schools. Data gathering instruments used were adversity quotient and metacognitive awareness questionnaires. There was a significant strong significant relationship between adversity quotient and mathematics performance. Also, a strong positive correlation was recorded between metacognition and mathematics performance. Thus, the higher students’ adversity quotient and metacognition are associated with higher mathematics performance.